ANTI-CYTOKINE (ANTI-TNF-ALPHA) THERAPY IN OPHTHALMOLOGY (REVIEW OF LITERATURE) - N. A. Gavrilopva; G. V. Lukina; N. S. Gadjiyeva; V. E. Shirokov; A. V. Fyodorov (Офтальмохирургия, 2015)
Analysis of the literature on anti-cytokine therapy demonstrates the effectiveness of this therapy, compared with conventional glucocorticosteroid and immunosuppressive therapy. Drugs with anti-cytokine mechanism of action can be used in Ophthalmology, as inhibitors of angiogenesis in neovascularization and anti-inflammatory therapy in uveitis. Route of administration of TNF inhibitors are intravenous and subcutaneous. They can be used as monotherapy or with the glucocorticosteroid and immunosuppressive therapy. From the literature it is obvious, that the effect of the use of this group of drugs are dose-dependent and they can be positive (anti-angiogenic and anti-inflammatory) and negative – toxic. In a comparative aspects, studies show, that Infliximab has more pronounced anti-inflammatory effect, but at the same time, use of Infliximab is more often with side effects and complications. According to different authors, doses that cause side effects, are not comparable. It seems that, localization of inflammatory process plays a role in the vascular tract of the eye (front, rear), etiologic factor, causing the inflammation and, of course, the intensity of cytokine responses. Therefore, the question, the efficacy and tolerability of anti-cytokine drugs are dose-dependent, and whether, there are other factors that influence on the success of treatment -remains open. To answer these questions is required a detailed study, investigating the influence of this group of drugs on the eye tissues, pathological angiogenesis processes depending on the drug, the dose and the conditions of its application, and testing of optimal dosage of drugs to avoid side effects